Population dynamics of wild rodents induce stochastic fadeouts of a zoonotic pathogen. (27th March 2017) - Guzzetta, Giorgio; Tagliapietra, Valentina; Perkins, Sarah E.; Hauffe, Heidi C.; Poletti, Piero; Merler, Stefano; Rizzoli, Annapaola
Summary: Stochastic processes play an important role in the infectious disease dynamics of wildlife, especially in species subject to large population oscillations. Here, we study the case of a free ranging population of yellow‐necked mice ( Apodemus flavicollis ) in northern Italy, where circulation of Dobrava‐Belgrade hantavirus (DOBV) has been detected intermittently since 2001, until an outbreak emerged in 2010. We analysed the transmission dynamics of the recent outbreak using a computational model that accounts for seasonal changes of the host population and territorial behaviour. Model parameters were informed by capture‐mark‐recapture data collected over 14 years and longitudinal seroprevalence data from 2010 to 2013. The intermittent observation of DOBV before 2010 can be interpreted as repeated stochastic fadeouts after multiple introductions of infectious rodents migrating from neighbouring areas. We estimated that only 20% of introductions in a naïve host population results in sustained transmission after 2 years, despite an effective reproduction number well above the epidemic threshold (mean 4·5, 95% credible intervals, CI: 0·65–15·8). Following the 2010 outbreak, DOBV has become endemic in the study area, but we predict a constant probability of about 4·7% per year that infection dies out, following large population drops in winter. In the absence of stochastic fadeout, viral prevalence is predicted to continue its growth to an oscillating equilibrium around a value of 24% (95% CI: 3–57). We presented an example of invasion dynamics of a zoonotic virus where stochastic fadeout have played a major role and may induce future extinction of the endemic infection. Abstract : Vital dynamics of animal populations may induce spontaneous extinction of infectious transmission chains, hampering pathogen invasion even when R0 is well above the epidemic threshold. The authors show an example of these effects in a colony of yellow‐necked mice where Dobrava Hantavirus has recently become endemic.